Effect of Potassium Permanganate on Staphylococcal Isolates Derived from the Skin of Patients with Atopic Dermatitis - Sigrid Lundgren; Andreas Sonesson (Medical Journals Sweden, 2024)
In atopic dermatitis (AD), Staphylococcus aureus frequently colonizes lesions, leading to superinfections that can then lead to exacerbations. The presence of biofilm-producing isolates has been associated with worsening of the disease. Potassium permanganate is used as a topical treatment of infected eczema, blistering conditions, and wounds. Little is known of its effects against microbes in AD skin. The aim of this study was to explore antibacterial and antibiofilm properties of potassium permanganate against staphylococcal isolates derived from AD skin. Viable count and radial diffusion assays were used to investigate antibacterial effects of potassium permanganate against planktonic staphylococcal isolates. The antibiofilm effects were assessed using biofilm assays and scanning electron microscopy. The Staphylococcus aureus isolates were completely killed when exposed to 0.05% of potassium permanganate. In concentrations of 0.01%, potassium permanganate inhibited bacterial biofilm formation. Eradication of established staphylococcal biofilm was observed in concentrations of 1%. Electron microscopy revealed dense formations of coccoidal structures in growth control and looser formations of deformed bacteria when exposed to potassium permanganate. This suggests antibacterial and antibiofilm effects of potassium permanganate against staphylococcal isolates derived from AD skin, when tested in vitro, and a potential role in the treatment of superinfected AD skin.